2022
DOI: 10.3389/fpls.2022.960641
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in nitrogen cycle and eco-efficient nitrogen management strategies in aerobic rice system

Abstract: Rice (Oryza sativa L.) is considered as a staple food for more than half of the global population, and sustaining productivity under a scarcity of resources is challenging to meet the future food demands of the inflating global population. The aerobic rice system can be considered as a transformational replacement for traditional rice, but the widespread adaptation of this innovative approach has been challenged due to higher losses of nitrogen (N) and reduced N-use efficiency (NUE). For normal growth and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 459 publications
0
4
0
1
Order By: Relevance
“…Sua formação ocorre principalmente durante o processo de desnitrificação, em que bactérias do solo convertem o nitrato em gases de N2O e N2 (Chen et al, 2019). A emissão de N2O é influenciada por fatores como disponibilidade de nitrato, teor de oxigênio no solo, umidade, temperatura e práticas de manejo agrícola (Farooq et al, 2022). O uso excessivo de fertilizantes nitrogenados, juntamente com práticas inadequadas de manejo do solo, pode aumentar as emissões de N2O.…”
Section: Perdas De N No Sistema Solo-planta-atmosferaunclassified
“…Sua formação ocorre principalmente durante o processo de desnitrificação, em que bactérias do solo convertem o nitrato em gases de N2O e N2 (Chen et al, 2019). A emissão de N2O é influenciada por fatores como disponibilidade de nitrato, teor de oxigênio no solo, umidade, temperatura e práticas de manejo agrícola (Farooq et al, 2022). O uso excessivo de fertilizantes nitrogenados, juntamente com práticas inadequadas de manejo do solo, pode aumentar as emissões de N2O.…”
Section: Perdas De N No Sistema Solo-planta-atmosferaunclassified
“…Soil N conservation and efficient utilization is highly challenging under such conditions. Flooding of paddy (rice) soils quickly depletes soil oxygen and results in Ammonia NH 3 volatilization while nitrate ( ) leaching is a major loss during aerobic conditions ( Farooq et al., 2022 ). An important strategy to enhance the efficiency of N is the integrated use of organic manures, and chemical fertilizers ( Bhardwaj et al., 2020a ; Bhardwaj et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The N cycle is predominately mediated by soil microbes, with the corresponding functional genes involved in the transformation of different nitrogen forms, such as NH 4 + , NO 3 − , and N 2 O [14], which might have affected rice yield [21]. However, soil microbes are rather sensitive to anthropogenic disturbance [22] and their structure and functions are often affected by farming practices [23]. It has been reported that fertilization application affects soil microbial community composition as well as plant growth [24].…”
Section: Introductionmentioning
confidence: 99%